Industrialization and the demand for mineral commodities - Martin Stuermer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2013)
What drives the long-term demand for mineral commodities? This paper provides empirical evidence on the long-run demand for mineral commodities since 1840. I extend the partial adjustment model to account for country-specific structures and technological change. I find that a one percent increase in manufacturing output leads to a 1.5 percent increase in the demand for aluminum and a one percent increase in the demand for copper. The estimated manufacturing output elasticities of demand for lead, tin, and zinc are far below one. The estimated price elasticities of demand are highly inelastic for all mineral commodities in the long run. My results suggest that industrialization in China, for example, will cause the consumption of aluminum and copper to increase at a considerably higher rate than the one of lead, tin, and zinc. All variables adjust slowly to equilibrium, which helps to explain the extended fluctuation in these markets.
Keywords: O13; Q31; N50; 330; Industrialization; elasticity of demand; nonstationary heterogenous panel; mineral commodities